2020
DOI: 10.1101/2020.10.08.20209148
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiology of sleep disorders during COVID-19 pandemic: A systematic scoping review

Abstract: Background: A growing burden of mental health problems has become a global concern amid the coronavirus disease (COVID-19) pandemic. Sleep disorders are major mental health problems associated with increased psychosocial stressors; however, no research synthesis is available on the epidemiology of it. In this systematic scoping review, we aimed to assess the current evidence on the epidemiological burden, associated factors, and interventions from the existing literature. Method: Seven major health databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 97 publications
1
19
0
1
Order By: Relevance
“…Recent studies have similarly shown that COVID-19 has affected mental health outcomes such as anxiety, depression, and post-traumatic stress symptoms [ 6 , 7 , 9 ]. Studies conducted in China in the early phase of COVID-19 found that the pandemic-affected individuals had a wide range of adverse psychological impacts of COVID-19 [ 21 , 22 , 23 , 24 , 25 ]. A recent meta-analysis by Salari et al., reported that the prevalence of stress 29.6%, the prevalence of anxiety 31.9%, and the prevalence of depression 33.7% globally [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have similarly shown that COVID-19 has affected mental health outcomes such as anxiety, depression, and post-traumatic stress symptoms [ 6 , 7 , 9 ]. Studies conducted in China in the early phase of COVID-19 found that the pandemic-affected individuals had a wide range of adverse psychological impacts of COVID-19 [ 21 , 22 , 23 , 24 , 25 ]. A recent meta-analysis by Salari et al., reported that the prevalence of stress 29.6%, the prevalence of anxiety 31.9%, and the prevalence of depression 33.7% globally [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have similarly shown that COVID-19 has affected mental health outcomes such as anxiety, depression, and post-traumatic stress symptoms 6,7,9 . Studies conducted in China in the early phase of COVID-19 found that the pandemic-affected individuals had a wide range of adverse psychological impacts of COVID-19 [21][22][23][24][25] . A recent meta-analysis by Salari et al, reported that the prevalence of stress 29.6%, the prevalence of anxiety 31.9%, and the prevalence of depression 33.7% globally 6 .…”
Section: Introductionmentioning
confidence: 99%
“…After the COVID-19 outbreak inception, the prevalence of insomnia is increasingly observed [ 26 ]. Ranging from 2.3 to 76.6%, with a pooled prevalence of 35.7%, insomnia is identified by a systematic review of a total of 78 studies [ 28 ], whereas the rate is found to be within 18–46.3% in Bangladesh [ 9 ]. The largest population-based study of the country reported 30.4%, 13.1%, and 2.8% rates of sub-threshold, moderate, and severe forms of insomnia, respectively, where the overall insomniac problem was 36.4% in that study [ 18 ].…”
Section: Discussionmentioning
confidence: 99%